2016
DOI: 10.1002/jssc.201501287
|View full text |Cite
|
Sign up to set email alerts
|

Separation and determination of flavonoids in three traditional chinese medicines by capillary electrophoresis with amperometric detection

Abstract: Flavonoids are important active ingredients in many traditional Chinese medicines. In this paper, capillary electrophoresis with amperometric detection was employed to separate and detect eight flavonoids, rutin, quercetrin, quercetin, kaempferol, kaempferide, catechin, apigenin, and luteolin, in a home-made capillary electrophoresis device. Under the separation voltage of 2000 V, the eight flavonoids could be completely separated within 33 min in 18 mM borax running buffer at pH 10.2. Good linear relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…23 Many studies have revealed that rutin is good for human health, such as antibacterial, antiulcer, anti-inflammatory, antiarrhythmia, antitumor, protective and expanding blood vessel. 24,25 Up to now, lots of analytical methods have been applied for the determination of rutin, including chemiluminescence, 26,27 high-performance liquid chromatography (HPLC), 28,29 capillary electrophoresis spectrophotometry, 30,31 UV-Vis spectrophotometry 32 and electrochemical methods. [33][34][35][36] In this work, Cu-doped carbon quantum dots (Cu-CQDs) were prepared by a facile one-step pyrolytic synthesis using Na 2 [Cu(EDTA)] as precursor.…”
Section: Introductionmentioning
confidence: 99%
“…23 Many studies have revealed that rutin is good for human health, such as antibacterial, antiulcer, anti-inflammatory, antiarrhythmia, antitumor, protective and expanding blood vessel. 24,25 Up to now, lots of analytical methods have been applied for the determination of rutin, including chemiluminescence, 26,27 high-performance liquid chromatography (HPLC), 28,29 capillary electrophoresis spectrophotometry, 30,31 UV-Vis spectrophotometry 32 and electrochemical methods. [33][34][35][36] In this work, Cu-doped carbon quantum dots (Cu-CQDs) were prepared by a facile one-step pyrolytic synthesis using Na 2 [Cu(EDTA)] as precursor.…”
Section: Introductionmentioning
confidence: 99%
“…Among these chemical compositions, flavonoids are the main active constituents present in the plant, which exhibited anxiolytic and antidepressant activity [20, 21]. Several methods have been developed for the determination of quercetin, luteolin, or apigenin in the plants, foods, and biological samples [2225]. However, to our knowledge, there has been no report on the simultaneous determination of quercetin, luteolin, and apigenin in animal plasma after oral administration of M. chamomilla extracts.…”
Section: Introductionmentioning
confidence: 99%
“…The LODs were ranged from 0.46 to 0.85 μM. . In reality, the materials of the detection electrodes employed in CE‐AD strongly influenced their performances (sensitivity and reproducibility).…”
Section: Methods Developmentmentioning
confidence: 99%